Integrating IoT Technology for Fire Risk Monitoring and Assessment in Residential Building Design - Usman Isah Abdullahi; Wei Zhang; Yidan Cao; Georges Irankunda (Buildings)
This research presents a pioneering framework to augment fire safety management within edifices by amalgamating real-time surveillance and adaptive evacuation methodologies. The proposed framework markedly enhances the efficacy of fire detection and the efficiency of evacuation processes. In an empirical investigation conducted on a 12-story residential structure in Wuhan, China, the implemented system achieved a 30% reduction in fire detection intervals and a 25% decrease in evacuation timeframes. The principal innovation of this framework resides in formulating an Improved Risk Index (ERI), which synthesizes real-time information garnered from environmental sensors, including temperature, smoke, and carbon monoxide concentrations, with architectural configurations and fire behavior to evaluate evacuation hazards. This system realized a detection accuracy rate of 95.2% and a 40% reduction in the necessity for manual inspections, surpassing the performance of conventional fire safety systems. The synthesis of real-time data with dynamic evacuation pathways enhanced emergency response times by equipping facility managers and emergency responders with instantaneous access to critical building intelligence. The framework complies with international and local fire safety regulations, ensuring its functional applicability across diverse types of buildings. This scholarly work offers a novel, scalable approach for improving fire safety management, potentially mitigating fire-induced damage and bolstering occupant safety within contemporary structures.